PENGEMBANGAN LKS BERBASIS MODEL LEARNING CYCLE 5E PADA MATERI BIOTEKNOLOGI - Saragih, Marlindoaman; Rajagukguk, Salome; Amelia, Marisa (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2024)
Development of Worksheet Based on The Larning Cycle 5E Model on Biotechnologycal Material, The development of LKS based on the 5E learning cycle on biotechnology material at Kartika 1-4 Pematangsiantar Private High School was motivated by the learning process which so far only used printed books and the use of LKS which was less interesting. This research aims to: 1) Find out the feasibility of the 5E learning cycle based LKS, 2) Find out students' responses to the 5E learning cycle based LKS being developed. The data collection instruments used in this research were validation sheets and questionnaire sheets. The validation results from two validators obtained an averege score of 85.3% in the Very Decent category, and the results based on students obtained an average score of 89.7% in the very good category. From the results of the research that has been carried out, it can be concluded that: 1) LKS based on the 5E learning cycle on biotechnology material developed at Kartika 1-4 Pematangsiantar Private High School are suitable for use, 2) Students' responses to the LKS based on the 5E learning cycle are very good